Active vocabulary stock of two-year-old Lithuanian children depending on upbringing conditions - Dailidienė , J. (Psichologija, 1971)
Our investigations have confirmed the point of view upheld by many investigators that the stock of children’s active vocabulary depends on their upbringing conditions. Both in families and educational establishments there may be certain conditions furthering or hindering the development of children’s speech. The studies of children’s active speech require special investigation of the character of conditions taking into account all the factors, ensuring the normal level of children’s speech development. In the conditions of social upbringing we can reach a high level of children’s active speech. It requires development of new methods and is the object of further investigation.